Hubungan Asupan Kalsium, Konsumsi Buah, Sayur dan Ikan Dengan Kadar Kolestrol Pada Pekerja Penanganan Prasarana Sarana Umum (PPSU) Kelurahan Cengkareng Timur - Mala Nimas Astuti; Nadiyah Nadiyah; Yulia Wahyuni; Harna Harna; Mury Kuswari (Lembaga Pengembangan Kinerja Dosen, 2023)
Cholesterol is a form of fat that has an important role for the body, but if the body has high cholesterol levels it will cause health problems in the form of fatty deposits which will be at risk of blockage of blood vessels. Based on the results of Basic Health Research, it shows that the prevalence in Indonesia with total cholesterol levels > 200 mg/dL is 39.8%, the high prevalence rate is one of the reasons for the increased mortality rate in Indonesia (RI Ministry of Health, 2018). Controlling cholesterol levels can be done by controlling diet such as intake of calcium, fruit, vegetables and fish. The research was conducted in Cengkareng Timur Village, from 19 October 2022 to 2 November 2022. The type of research is quantitative which is analytic using a cross sectional research design, the research sample is 84 respondents. Data analysis used the Spearman correlation test. Based on the research results, it was found that there was a relationship between calcium intake and cholesterol levels (p=0.000) with a value of r = -0.924, there was a relationship between vegetable and fruit consumption and cholesterol levels (p=0.002) with a value of r = -0.496, and there was a relationship between consumption fish with cholesterol levels (p=0.001) with a value of r = -0.351. Workers handling public facilities infrastructure in Cengkareng Timur Village are expected to be able to consume fruits and vegetables because workers' consumption of fruits and vegetables is less than 400 g/day accompanied by a healthy lifestyle.